PENGARUH KONSUMSI MINUMAN BERSODA TERHADAP TEKANAN DARAH PADA WANITA USIA SUBUR USIA ≥ 18 TAHUN DI RW 04 KELURAHAN AREN JAYA KOTA BEKASI - Lusty Frisky Wilyagripina (2021)
The prevalence of hypertension in Indonesia in 2018 was 34.1% and the prevalence of hypertension in women was 36.9%. Hypertension not only attacks the elderly but at productive age can also have hypertension. Hypertension in women of reproductive age can be caused by a family history of hypertension, food intake and use of birth control pills. Consumption of soft drinks can increased blood pressure because of the caffeine, sodium and fructose content in it. The purpose of this study was to determine the effect of consumption of cola soft drinks on blood pressure in women of reproductive age (aged ≥ 18 years). This research is a quantitative study using a quasi experimental research design. The population in this study were women of reproductive age (aged ≥ 18 years) in RW 04, Aren Jaya Village, Bekasi which numbered 1,311 people. The sampling technique used was purposive sampling. The statistical test used was the paired t-test. The results of statistical tests between systolic and diastolic blood pressure before and after the intervention showed p value 0.001 and 0.021, which means that there is a significant difference, so that consumption of soft drinks can increased blood pressure in women of reproductive age (aged ≥ 18 years).